Mechanically mixing and oxidation layer induced by different contact surface of columnar Cu under dry sliding condition - Qiang Qiang Chen; Qian Li; Jian Shang (Materials Research Express, 2024)
The dry sliding behavior of columnar Cu with vertical orientation (VO) and horizontal orientation (HO) coupling with 1045 steel was studied. The results show that when the sliding distance is 672 m, the friction coefficient of HO Cu is 0.21 lower than that of VO Cu, and the wear rate is reduced by 0.63·10 ^−6 g·N ^−1 m ^−1 ; when the sliding distance is 1344 m, the friction coefficient of HO Cu is 0.10 lower than that of VO Cu, and the wear rate is reduced by 0.31·10 ^−6 g·N ^−1 m ^−1 . The Fe _3 O _4 oxide was detected on the wear surface of HO Cu by Raman spectroscopy. And it plays a greater role in lubrication and protection of friction layer. On the worn surface of VO Cu, there is obvious softening caused by thermal activation or composition mixing. This softening will lead to a significant decrease in the strength of the friction layer, and the friction coefficient and wear loss increase negatively.